PENINGKATAN LITERASI KEUANGAN PADA MASYARAKAT DESA CIGUDEG DALAM PEMBUATAN LAPORAN KEUANGAN SEDERHANA (Komunitas Pengusaha Berjenjang Produk Oriflame) - R Ai Lutfi Hidayat; Juitania Budiono; Fitri Sagantha; Andri S; Adi Sofyana Latif (S1 Accounting Program, Universitas Pamulang, 2019)
The problem that is owned by entrepreneurs who are members of the tiered oriflamm product community in Cigudeg village is the lack of understanding of recording financial statements, especially simple financial statements. The service team decided to provide continuous training for 1 month which was divided into 3 periods, namely the 13th of 20.20 and October 27, 2019. This continuity needs to be done to provide a deeper effect for the trainees so that the trainees can maximize the training material to be reversed in the business being run, so that all income and expenses can be neatly recorded, which in turn can find out how much money you get each month. The material will be provided by Pamulang university lecturers who are experienced in teaching Accounting. In addition, the determination of sources is also based on the background of each instructor so that the instructor can provide teaching materials in a way that is easily understood by the trainees so that the trainees can capture the concepts in recording financial statements simply and apply these records in conducting their business with recording every day. Provision of teaching materials continuously has not given maximum results as the service team expected, so it was decided that training needs to be held longer and in-depth again to have a significant influence on the ability of entrepreneurs who are members of the oriflamme community so that the bookkeeping can be run by each member of both lines above and below the line in the community in the village of Cigudeg. Keywords: Simple financial repor; Financial literacy